Exploring International Graduate Students’ Experiences, Challenges, and Peer Relationships: Impacts on Academic and Emotional Well-being - Lorenzetti, Diane; Lorenzetti, Liza; Nowell, Lorelli; Jacobsen, Michele; Clancy, Tracey; Freeman, Georgina; Oddone Paolucci, Elizabeth (Journal of International Students, 2023)
As the number of international students in higher education continues to grow, so do concerns regarding systemic obstacles, discrimination, and social isolation that can impede students’ academic success. Peer mentorship has been shown to support graduate students through academic socialization and achievement in higher education (Lorenzetti et al., 2019). The purpose of this study was to explore the transitional experiences of international graduate students, and the extent to which peer-mentoring relationships can support academic and emotional well-being. Researchers interviewed 13 international graduate students from 3 professional faculties at a research-intensive Canadian university. International students described academic and intersectional challenges experienced while navigating and adapting to new environments and how these impacted both academic outcomes and students’ well-being. Relationships with peers were viewed as an essential means by which students could access academic and psychosocial supports necessary to adjust to and thrive in their new educational and cultural environments.